Morphological and molecular motifs of fibrosing pulmonary injury patterns. (25th September 2019) - Jonigk, Danny; Stark, Helge; Braubach, Peter; Neubert, Lavinia; Shin, Hoen‐oh; Izykowski, Nicole; Welte, Tobias; Janciauskiene, Sabina; Warnecke, Gregor; Haverich, Axel; Kuehnel, Mark; Laenger, Florian
Abstract: Interstitial lung diseases encompass a large number of entities, which are characterised by a small number of partially overlapping fibrosing injury patterns, either alone or in combination. Thus, the presently applied morphological diagnostic criteria do not reliably discriminate different interstitial lung diseases. We therefore analysed critical regulatory pathways and signalling molecules involved in pulmonary remodelling with regard to their diagnostic suitability. Using laser‐microdissection and microarray techniques, we examined the expression patterns of 45 tissue‐remodelling associated target genes in remodelled and non‐remodelled tissue samples from patients with idiopathic pulmonary fibrosis/usual interstitial pneumonia (IPF/UIP), non‐specific interstitial pneumonia (NSIP), organising pneumonia (OP) and alveolar fibroelastosis (AFE), as well as controls (81 patients in total). We found a shared usage of pivotal pathways in AFE, NSIP, OP and UIP, but also individual molecular traits, which set the fibrosing injury patterns apart from each other and correlate well with their specific morphological aspects. Comparison of the aberrant gene expression patterns demonstrated that (1) molecular profiling in fibrosing lung diseases is feasible, (2) pulmonary injury patterns can be discriminated with very high confidence on a molecular level (86–100% specificity) using individual gene subsets and (3) these findings can be adapted as suitable diagnostic adjuncts.